2015
DOI: 10.1111/hel.12243
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory Effects of Capsaicin and Piperine on Helicobacter pylori‐Induced Chronic Gastritis in Mongolian Gerbils

Abstract: These results suggest that capsaicin and piperine have anti-inflammatory effects on H. pylori-induced gastritis in gerbils independent of direct antibacterial effects and may thus have potential for use in the chemoprevention of H. pylori-associated gastric carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 51 publications
(67 reference statements)
2
33
0
Order By: Relevance
“…Thus, there were correlation between existence of peak and anti-inflammatory activity. In the previous study, capsaicin included in other Capsicum plants has been known to show anti-inflammatory activity (23,24). In this study, we tried to measure of HPLC chromatogram of capsaicin in the same HPLC condition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there were correlation between existence of peak and anti-inflammatory activity. In the previous study, capsaicin included in other Capsicum plants has been known to show anti-inflammatory activity (23,24). In this study, we tried to measure of HPLC chromatogram of capsaicin in the same HPLC condition.…”
Section: Discussionmentioning
confidence: 99%
“…It also is a major compound of capsaicinoids (alkaloid) that are widely applied in pharmaceutical and clinical product [7]. As one of the natural products, it was reported that capsaicin has therapeutic properties currently employed as antitumor [8], anti-mutagenic [9], antioxidant compounds [7], antimicrobial [3], anticancer [10], cardio-protection [11], antiobesity [12], anti-diabetic [13], and antiinflammatory effect [14].…”
Section: Introductionmentioning
confidence: 99%
“…(d) Quantification of infiltration of inflammatory cells. The degree of neutrophil or mononuclear cell infiltration was scored for 3 of the 6 (G11), 8 (G1, G2, G3, G6, G7, and G10), 12 (G8 and G12), and 15 (G4) gerbils on a four‐point scale (0 to 3), as described previously . In gerbils with 50 weeks of H. pylori infection, the infiltration of neutrophils and mononuclear cells remained, even 30 weeks after eradication.…”
Section: Resultsmentioning
confidence: 99%
“…The sliced FFPE samples were deparaffinized, and were stained with hematoxylin and eosin. The degree of infiltration of inflammatory cells, namely neutrophils and mononuclear cells, was scored for three of the six (G11), eight (G1, G2, G3, G6, G7, and G10), 12 (G8 and G12), and 15 (G4) gerbils on a four‐point scale (0 to 3), as described previously . All the animal experiments were approved by the committee for Ethics in Animal Experimentation at the National Cancer Center.…”
Section: Methodsmentioning
confidence: 99%